Managing systematic and ethical public relations - McEbreath, Mark P. (Wm. C. Brrown communications, Inc., 1993)
Introduction to managing systematic and ethical public relations management expectations for public relations vary dramatically a brief, systematic history of public relations
Keywords: Mercadeo; Relaciones Públicas